PERBANDINGAN HASIL BELAJAR FISIKA ANTARA PEMBELAJARAN YANG MENGGUNAKAN LEARNING CYCLE 5E DENGAN PROBLEM BASED LEARNING - Eria Puspita; Agus Suyatna; Viyanti - (Jurnal Pembelajaran Fisika, 2012)
The success in the teaching learning process is influenced by the effectiveness of learning method which is able improve the student’s achievement. The objectives of this research were to find out the improvement of physic achievement between the students who are taught through learning cycle 5E and those who are taught through problem based learning, and to find out the different on the average score in learning physic between the students who are taught through learning cycle 5E and those who are taught through problem based learning. The research design was Non-Equivalent pretest-posttest design. The samples of this research were the students in the class X6 and X9. The samples were selected by using purposive sampling technique. Finally, based on the result, it can be concluded that,(1) There is an improvement of students achievement on the learning cycle 5E method, (2) There is an improvement of students achievement on the problem based learning, (3) There is a difference on the score in learning physic between the students who are thought trough learning cycle 5E and those who are taught through problem based learning.Keyword: Achievement, learning cycle 5E, Problem Based Learning